2022
DOI: 10.1111/joim.13593
|View full text |Cite
|
Sign up to set email alerts
|

Global guidance for the recognition, diagnosis, and management of tumor‐induced osteomalacia

Abstract: Tumor‐induced osteomalacia (TIO) is a rare paraneoplastic syndrome caused by mesenchymal tumors that secrete fibroblast growth factor 23 (FGF23). Patients present with progressive bone pain, muscle weakness, and fragility fractures. TIO is characterized by hypophosphatemia, excess renal phosphate excretion, and low/inappropriately normal 1,25‐dihydroxyvitamin D (1,25(OH)2D) levels. Rarity and enigmatic clinical presentation of TIO contribute to limited awareness among the medical community. Accordingly, approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 122 publications
(245 reference statements)
4
57
0
1
Order By: Relevance
“…Monitoring aerobic glycolysis in tumor tissue might lead to improved methods for diagnosing and treating cancer ( Ma et al, 2022 ; Raskov et al, 2022 ). Molecular imaging is an emerging interdisciplinary subject in imaging, medicine, and molecular biology ( Jan De Beur et al, 2022 ). Early detection, tailored treatment, and real-time tumor monitoring will benefit from non-invasive molecular imaging of glucose metabolism in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring aerobic glycolysis in tumor tissue might lead to improved methods for diagnosing and treating cancer ( Ma et al, 2022 ; Raskov et al, 2022 ). Molecular imaging is an emerging interdisciplinary subject in imaging, medicine, and molecular biology ( Jan De Beur et al, 2022 ). Early detection, tailored treatment, and real-time tumor monitoring will benefit from non-invasive molecular imaging of glucose metabolism in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the tumor cannot be localized or completely resected, image guided ablation combined with cryoablation or radiofrequency ablation can be used as an alternative treatment 9,13 . Small molecule targeted drugs can significantly improve symptoms and inhibit disease progression in unresectable, relatively concealed, or unidentified PMTs, but there is still a lack of evidence regarding their long‐term efficacy and safety 14,15 . The anti‐FGF23 monoclonal antibody (burosumab) has been proven to be safe and effective in improving objective indicators and symptoms of TIO 15 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…9,13 Small molecule targeted drugs can significantly improve symptoms and inhibit disease progression in unresectable, relatively concealed, or unidentified PMTs, but there is still a lack of evidence regarding their long-term efficacy and safety. 14,15 The anti-FGF23 monoclonal antibody (burosumab) has been proven to be safe and effective in improving objective indicators and symptoms of TIO. 15 The pan FGFR tyrosine Other Tumors Caution should still be exercised before diagnosing osteomalacia caused by other tumors, unless it is confirmed that they produces FGF23 separately without the coexistence of phosphate mesenchymal tumors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…If the above alternatives fail and the neuroendocrine origin of the phosphaturic tumor has been confirmed, radioactive treatment with products such as lutetium-dotatate, which combines a somatostin analogue (octreotate) with Lu177, a beta emitter with tumor-cytolytic potential, can be chosen [ 73 ]. Very recently, the Committee for Medicinal Products for Human Use of the European Medicines Agency has recommended that burosumab be approved for the treatment of FGF23-related hypophosphatemia in TIO associated with phosphaturic mesenchymal tumors that cannot be curatively resected or localized in children and adolescents aged 1 to 17 years and in adults [ 74 , 75 , 76 ]. Lastly, other drugs are in the experimental phase, such as infigratinib (inhibitor of tyrosine kinases involved in the signal of FGFR1, FGFR2, and FGFR3), a drug approved for the treatment of advanced cholangiocarcinoma [ 77 , 78 , 79 ].…”
Section: Etiology Of Osteomalaciamentioning
confidence: 99%